2003
DOI: 10.1002/icd.308
|View full text |Cite
|
Sign up to set email alerts
|

Possible antecedents and developmental implications of shame in young girls

Abstract: The objectives of this study were to assess the effects of parenting style and child emotionality on the development of proneness to shame in young girls, and the mediating effect of shame on the development of adjustment problems. Eighty-eight girls were assessed twice, at 3 and 5 years of age, along with their mothers and fathers. Shame was assessed by observations (reactions to failure and criticism); parenting style and child emotions (fearfulness, sadness, anger) were measured using parent reports; and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
1
28
2
Order By: Relevance
“…In contrast, maltreated boys tended to exhibit less shame and pride than nonmaltreated boys, suggesting an important gender difference. Moreover, Mills (2003) found that preschool-age girls were more likely to exhibit shame when their parents used an authoritarian parenting style, which has been related to harsh physical punishment (Frias-Armenta & McCloskey, 1998). Examining older children, harsh parenting at age 9 was found to predict parental rejection at 15 (Stuewig & McCloskey, 2005).…”
mentioning
confidence: 99%
“…In contrast, maltreated boys tended to exhibit less shame and pride than nonmaltreated boys, suggesting an important gender difference. Moreover, Mills (2003) found that preschool-age girls were more likely to exhibit shame when their parents used an authoritarian parenting style, which has been related to harsh physical punishment (Frias-Armenta & McCloskey, 1998). Examining older children, harsh parenting at age 9 was found to predict parental rejection at 15 (Stuewig & McCloskey, 2005).…”
mentioning
confidence: 99%
“…Among minors, a central role is played by shame, humiliation and anger, together with specific representations of the self (Lewis 1971;Tangney and Dearing 2003). Maltreated children, especially those abused, characteristically experience shame (Loader 1998); moreover, they have parents with a negative or an authoritarian parental style (Alessandri and Lewis 1993;Alessandri and Lewis 1996;Belsky and Domitrovich 1997;Lewis 1992;Margari et al 2013;Mills 2003;Stuewig and McCloskey 2005).…”
Section: The Role Of the Emotional Processesmentioning
confidence: 99%
“…These beliefs about the self elicit shame (Lewis 1992) and lead these children, who continue over time to be maltreated, to develop emotional processes different from those of not maltreated ones and which can be different whether the victim is a boy or a girl (Alessandri and Lewis 1996). Indeed, Mills (2003) highlighted that preschool girls are more likely to experience shame when they experience an authoritarian parental style, associated with physical punishments (Frias-Armenta and McCloskey 1998). With respect to older minor, severe parenting at age nine is predictive of parental rejection at 15 years old, which is associated with an increased propensity to experience shame at the same age (Stuewig and McCloskey 2005).…”
Section: The Role Of the Emotional Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous groups of maltreated children, which have included neglected as well as physically and sexually abused children, exhibit elevated levels of shame [83,[89][90][91]. Similarly, children whose parents are negative and rejecting or who use an authoritarian style of parenting are at increased risk of exhibiting shame [83,89,[92][93][94].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%